STIMULASI PERKEMBANGAN KOGNITIF ANAK USIA DINI MELALUI MEDIA KONKRET DI TKK NEGERI HARAPAN BANGSA KOELODA - Tanty Woga; Angelina Kurnia Juita (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2023)
Cognitive development is the basis for the development of intelligence in early childhood. The cognitive development of a person or child is related to how indifidu can learn, pay attention, observe, and estimate. This development is related to how this is in the field of learning and thinking about the environment. To examine more deeply about the cognitive development of early childhood, we practice teaching directly in schools or PAUD institutions. According to Piaget, children actively build their own cognitive world. Children are not passive to receive information, but rather play an active role in nature to compile their knowledge about reality. Cognitive development is the basis for the development of intelligence in early childhood. The cognitive development of a person or child is related to how indifidu can learn, pay attention, observe, and estimate. This development is related to how this is in the field of learning and thinking about the environment. To examine more deeply about the cognitive development of early childhood, we practice teaching directly in schools or PAUD institutions. According to Piaget, children actively build their own cognitive world. Children are not passive to receive information, but rather play an active role in nature to compile their knowledge about reality.